A new variety of Bromus flexuosus (Poaceae: Pooideae Bromeae, sect. Bromopsis) - Planchuelo, Ana Maria Rosa (2010)
Bromus flexuosus was evaluated morphologically using discriminant characters and phenetic cluster analysis. The results support the recognition Bromus flexuosus var. famatinensis Planchuelo as a new variety. A morphological description, habitat, geographical distribution, and representative specimens of both varieties of Bromus flexuosus are included along with statistical information, a key, synonymies, species descriptions, illustrations, and citations of representative specimens of allied species (B. lanatus Kunth and B. modestus Renvoize) growing in the Central Andes.